Transitioning to an unfamiliar medium of instruction: Strategies used by Rwandan primary school teachers to enable learning - Ndabaga, Eugene; Kwok, Pui Ki Patricia; Sabates, Ricardo; Ntabajyana, Sylvestre; Bizimana, Barthelemy (International journal of educational research, 2023)
•Teachers play crucial roles in achieving the national policy visions envisaged.•Rwandan teachers have suggested a wide range of innovative strategies to support students learning in an unfamiliar MOI.•Engaging with teacher perspectives is the key to develop more context-sensitive strategies to support student learning. In many post-colonial African countries, teaching using international languages as the medium of instruction (MOI) places particular challenges with respect to engaging students in learning. This paper explores pedagogical strategies used by Rwandan teachers in primary schools to support their students’ learning subject content when English is the MOI. Findings from 24 interviews and four focus group discussions in four 12-year Basic Education schools indicate that teachers use a rich repertoire of strategies to support students’ learning, which can be clustered into four key themes: (1) communication in an unfamiliar MOI, (2) strategies for visual demonstration (3) strategies for engaging students, and (4) commitment to supporting students with different needs. The implications of these findings are discussed.